Open defecation free: where do we need to focus ? - Adhikari, Ramesh; Ghimire, Sudha (Health Prospect, 2020)
Background Despite major national and international efforts, many households in Nepal (as in other low-income and middle-income countries) still lack toilets. This paper assesses various determinants that act as main contributing factors because of which households in Nepal still do not have toilets. Methods Data from the Nepal Demographic and Health Survey (NDHS) 2016 was used for this study. Bivariate analysis was done to assess the association between dependent variables (toilet status- having and not having toilets in the household) and independent variables (demographic, socio-economic and geographical characteristics) using Chi-square test. Then, a multi variate logistic regression model was used to assess significant predictors for a household not having a toilet after controlling other variables. Results Out of the total number of sampled households (11040), nearly a fifth (18%) belonged to province no. 2, where nearly half of the households (49%) did not have toilet facilities. Similarly, households in rural areas were found to be less likely to have toilets than households in urban areas (aOR=1.56, CI1.35-1.80). In the Terai, households were almost ten times as likely not to have toilets (aOR=9.65, CI6.56-14.19) as compared to households in the mountain region. Furthermore, there is a strong positive association between households with toilets and their economic status. Poorest (aOR=15.19, CI11.26-20.47), poorer (aOR=8.75, CI6.89-11.11) and middle income (aOR=5.12, CI4.15-6.32) households were less likely to have a toilet than richer or richest households. Conclusions Despite some real achievements and progress in Open Defecation Free (ODF) status, Nepal still has a large number of residences without a toilet. Thus, it is crucial to address all the multifaceted factors such as geographical, provincial and economic when considering sustainable ODF programming.